Engineering Management - Pedro García Márquez, Fausto; Lev, Benjamin (IntechOpen, 2013)
The Engineering Management book synthesises the engineering principles with business practice, i.e. the book provides an interface between the main disciplines of engineering/technology and the organizational, administrative, and planning abilities of management. It is complementary to other sub-disciplines such as economics, finance, marketing, decision and risk analysis, etc. This book is intended for engineers, economics and researchers who are developing new advances in engineering management, or who employ the engineering management discipline as part of their work. The authors of this volume describe their pioneering work in the area or provide material for case studies successfully applying the engineering management discipline in real life cases.